Role of PTEN in basal cell derived lung carcinogenesis. Issue 10 (26th April 2013) - Malkoski, Stephen P.; Cleaver, Timothy G.; Thompson, Joshua J.; Sutton, Whitney P.; Haeger, Sarah M.; Rodriguez, Karen J.; Lu, Shi‐Long; Merrick, Daniel; Wang, Xiao‐Jing
Abstract Lung adenocarcinoma (AdC) and lung squamous cell carcinoma (SCC) are the most common non‐small cell lung cancer (NSCLC) subtypes, however, most genetic mouse models of lung cancer produce predominantly, if not exclusively, AdC. Whether this is secondary to targeting mutations to the distal airway cells or to the use of activating Kras mutations that drive AdC formation is unknown. We previously showed that targeting KrasG12D activation and transforming growth factor β receptor type II (TGFβRII) deletion to airway basal cells via a keratin promoter induced formation of both lung AdC and SCC. In this study we assessed if targeting phosphatase and tensin homologue (PTEN) deletion to airway basal cells could initiate lung tumor formation or increase lung SCC formation. We found that PTEN deletion is capable of initiating both lung AdC and SCC formation when targeted to basal cells and although PTEN deletion is a weaker tumor initiator than KrasG12D with low tumor multiplicity and long latency, tumors initiated by PTEN deletion were larger and displayed more malignant conversion than KrasG12D initiated tumors. That PTEN deletion did not increase lung SCC formation compared to KrasG12D activation, suggests that the initiating genetic event does not dictate tumor histology when genetic alterations are targeted to a specific cell. These studies also confirm that basal cells of the conducting airway are capable of giving rise to multiple NSCLC tumor types. © 2013 Wiley Periodicals, Inc.